1994
DOI: 10.1002/j.1460-2075.1994.tb06597.x
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of human erythrocyte aquaporin CHIP.

Abstract: Water‐permeable membranes of several plant and mammalian tissues contain specific water channel proteins, the ‘aquaporins’. The best characterized aquaporin is CHIP, a 28 kDa red blood cell channel‐forming integral protein. Isolated CHIP and Escherichia coli lipids may be assembled into 2‐D crystals for structural analyses. Here we present (i) a structural characterization of the solubilized CHIP oligomers, (ii) projections of CHIP arrays after negative staining or metal‐shadowing, and (iii) the 3‐D structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
0
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 38 publications
10
70
0
1
Order By: Relevance
“…Second, the projection of LB and LE into the core of the protein (the hourglass model) was suggested by mutagenesis data , a feature now clearly resolved at 4.5 A Ê in the 3D map of AQP1 (Mitsuoka et al, 1999). Third, analytical ultracentrifugation, freeze fracture, single particle analysis, scanning transmission electron microscopic mass analysis and electron crystallography of several members of the family indicate a tetrameric biological unit (Beuron et al, 1995;Hasler et al, 1998;Ko È nig et al, 1997;Ringler et al, 1999;Smith & Agre, 1991;Verbavatz et al, 1993;Walz et al, 1994). The reports of monomeric GlpF from E. coli (GLPF ECOLI), and the monomeric status of some functional AQPcic mutants (AQPcic is an AQP from Cicadella viridis, g1279358 in GENBANK) (Lagre Âe et al, 1998(Lagre Âe et al, , 1999) need yet to be con®rmed by direct structural studies.…”
Section: Discussionmentioning
confidence: 93%
“…Second, the projection of LB and LE into the core of the protein (the hourglass model) was suggested by mutagenesis data , a feature now clearly resolved at 4.5 A Ê in the 3D map of AQP1 (Mitsuoka et al, 1999). Third, analytical ultracentrifugation, freeze fracture, single particle analysis, scanning transmission electron microscopic mass analysis and electron crystallography of several members of the family indicate a tetrameric biological unit (Beuron et al, 1995;Hasler et al, 1998;Ko È nig et al, 1997;Ringler et al, 1999;Smith & Agre, 1991;Verbavatz et al, 1993;Walz et al, 1994). The reports of monomeric GlpF from E. coli (GLPF ECOLI), and the monomeric status of some functional AQPcic mutants (AQPcic is an AQP from Cicadella viridis, g1279358 in GENBANK) (Lagre Âe et al, 1998(Lagre Âe et al, , 1999) need yet to be con®rmed by direct structural studies.…”
Section: Discussionmentioning
confidence: 93%
“…Velocity sedimentation of detergent-solubilized membrane proteins is technically difficult, because the protein standards are freely soluble in water (21). Nevertheless, ultrastructural studies confirmed that AQP1 is tetrameric in the plasma membranes of transfected cells (22) and in reconstituted membrane crystals (23,24). AqpZ forms particularly stable tetramers which remain noncovalently associated even in SDS (1).…”
Section: Discussionmentioning
confidence: 94%
“…The mass-per-length is a useful if not essential parameter defining the structure of filaments [25], indicating the number of strands present [26][27][28][29] and in the case of helices restricting the number of possible assembly rules [30][31][32]. Similarly, the massper-area defines the unit cell stoichiometry in 2D crystals or the number of layers in a sheet-like structure [33][34][35][36], information that is otherwise only accessible by chance at their edges, or by atomic force microscopy [36] [37]. Further, in conjunction with a lipid assay by analytical ultracentrifugation mass-per-area measurements can be used to confirm the predicted packing of membrane proteins in two-dimensional crystalline arrays [35].…”
Section: Introductionmentioning
confidence: 99%